The Influence of Leadership, Incentives and Work Environment on Loyalty Administrative Employees of Faculty Offices at UIN Syahada Padangsidimpuan - Nasution , Samsinar (PT. Sharia Journal and Education Center, 2024)
This study aims to determine the effect of leadership, incentives and work environment both partially and jointly on the loyalty of the administrative staff of the Faculty office at Ahmad Dahlan University, Yogyakarta. This research is a quantitative research. Data collection using a questionnaire method (questionnaire) that has been tested for validity and reliability, while data analysis is done using multiple linear regression analysis. The sample of this study was all administrative employees in all faculties at Ahmad Dahlan University, amounting to 60 employees with sample collection techniques using saturated samples, so the sample size in this study amounted to 60 employees. The results showed that: 1) Leadership has a significant effect on employee loyalty, this is indicated by the results of the t test of 3.123 with a significance of 0.003. 2) Incentives have a negative and significant effect on employee loyalty, this is indicated by the results of t count of -2,378 with a significance of 0.021. 3) The work environment has no effect on employee loyalty. 4) Leadership, incentives and work environment together have a significant effect on employee loyalty, this is indicated by an F count of 3.647 with a significance of 0.0.018 with a regression equation Y = -2.315 + 0.432X1-0.333X2 + 0.099X3 + e. With a large effect of 0.16.3%, while the remaining 83.7% is influenced by other independent variables that are not observed.